2019
DOI: 10.1109/access.2019.2895092
|View full text |Cite
|
Sign up to set email alerts
|

SGS: Safe-Guard Scheme for Protecting Control Plane Against DDoS Attacks in Software-Defined Networking

Abstract: Software-defined networking (SDN) achieves flexible and efficient network management by decoupling control plane from the data plane, where the controller with a global network view is responsible for planning routing for packets. However, the centralized design makes the controller become a potential bottleneck, and adversaries can exploit this vulnerability to launch distributed denial-of-service (DDoS) attacks to the controller. Existing solutions are fundamentally based forged traffic analysis, increasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(49 citation statements)
references
References 25 publications
0
49
0
Order By: Relevance
“…In addition, the knearest neighbor algorithm (KNN) is also a simple and effective machine learning algorithm, which classifies flows by measuring the abstract distance between traffic feature vectors. Peng et al [14] proposed the abnormal traffic detection algorithm, DPTCM-KNN. This algorithm can effectively improve the accuracy of abnormal flow detection, and at the same time reduce the false alarm rate in the process of DDoS detection.…”
Section: A Researches On Ddos Detection and Defense Methodsmentioning
confidence: 99%
“…In addition, the knearest neighbor algorithm (KNN) is also a simple and effective machine learning algorithm, which classifies flows by measuring the abstract distance between traffic feature vectors. Peng et al [14] proposed the abnormal traffic detection algorithm, DPTCM-KNN. This algorithm can effectively improve the accuracy of abnormal flow detection, and at the same time reduce the false alarm rate in the process of DDoS detection.…”
Section: A Researches On Ddos Detection and Defense Methodsmentioning
confidence: 99%
“…The results of the study indicated that the proposed scheme is a practical approach. SGS, a safeguard scheme for protecting the control plane against DDoS attacks in SDN, is proposed in [26]. SGS uses a controller's clustering method to deploy multiple controllers in the control plane.…”
Section: B Machine Learning Approachmentioning
confidence: 99%
“…Experimental results show that this mechanism performs well in reducing TCAM occupation. Wang et al [12] proposed a safe-guard scheme (SGS), which deployed multiple controllers on the control plane through clustering algorithm to improve the defense capability of the control plane. However, this scheme required high performance of the switch.…”
Section: Related Workmentioning
confidence: 99%